DEVELOPMENT OF PAPER-BASED, LASER INDUCED GRAPHENE NONENZYMATIC BIOSENSOR FOR GLUCOSE DETECTION - Nunes, Vitor Manuel Vieira (2024)
Diabetes mellitus is a persistent metabolic condition that endures throughout an indi- vidual's life. Glucose and insulin play a crucial role in the management and regulation of this illness. Frequently, a variety of laboratory tests are utilized for diagnosing and managing dia- betes. One of the key diagnostic criteria is the measurement of blood glucose concentration. New studies aim for a non-evasive testing of glucose concentration in other body fluids, spe- cifically sweat. This thesis addresses the issue of expensive glucose sensors by developing a sensor employing nickel nanoparticles (NiNPs), a more affordable transition metal, and inves- tigating a substitute for silver (the metal mainly used in biomedical applications), along with Laser-Induced Graphene (LIG), a fast and straightforward method for generating graphene, on paper substrates. To begin with, the LIG technique provides a quick and easy way to create highly conductive graphitized material, which is valuable for sensing applications, without re- quiring costly or complicated fabrication methods. Furthermore, it enables the creation of LIG on paper, which is a more eco-friendly, adaptable, cost-effective, and readily available option compared to other frequently utilized materials. A low-cost nickel precursor was chosen for creating NiNPs using a laser, which showed great catalytic activity for glucose oxidation in non- enzymatic detection. Consequently, NiNPs and LIG composites were fabricated together in a single step, enabling the mass production of sensors. The LIG electrode that had obtained the best results had a sheet resistance value of only 18.24 Ohm/sq. The sensor exhibited strong electrochemical performance during cyclic voltammetry assessment. The biosensor showed the ability to detect glucose, but did not reach the required analytical levels within sweat range (20 μM to 1.79 mM), more tests need to be carried out to achieve more favorable results and to find a way to achieve greater deposition of NiNPs on the electrode that will be in contact with glucose.